Determinants of Public Participation in The Development of Priority Halal Tourism - Hannum, Misbah; Harahap, Isnaini; Soemitra, Andrew (Dinar : Jurnal Ekonomi dan Keuangan Islam, 2024)
This study aims to determine the factors that influence community participation in the development of halal tourism in Puncak Koto Panjang, Pasaman Regency.This study uses a quantitative method with multiple linear regression analysis methods. using SPSS 25 software. The population in the study were stakeholders of Puncak Koto Panjang in 2024. The data collection technique used primary data obtained by distributing questionnaires to 383 stakeholder respondents. While secondary data was taken through journals, books, or previous research related to this study.The results of the study showed that the Economic factor (X1) has a significant influence on the development of halal tourism in Puncak Koto Panjang (t count 1.830 t table 0.675), the educational factor has a significant influence on the development of halal tourism in Puncak Koto Panjang (t count 5.998 t table 0.675), socio-cultural factors have a significant influence on the development of halal tourism in Puncak Koto Panjang (t count 5.303 t table 0.675) while the leader factor and social motivation factors do not affect the development of Puncak Koto Panjang tourism. This research is expected to provide practical contributions to the development of halal tourism at Puncak Koto Panjang so that it can develop further, and visitors can feel satisfied with their visit.